Exosome as a Vehicle for Delivery of Membrane Protein Therapeutics, PH20, for Enhanced Tumor Penetration and Antitumor Efficacy - Hong, Yeonsun; Nam, Gi-Hoon; Koh, Eunee; Jeon, Sangmin; Kim, Gi Beom; Jeong, Cherlhyun; Kim, Dong-Hwee; Yang, Yoosoo; Kim, In-San (WILEY-V C H VERLAG GMBH, 2018)
As biochemical and functional studies of membrane protein remain a challenge, there is growing interest in the application of nanotechnology to solve the difficulties of developing membrane protein therapeutics. Exosome, composed of lipid bilayer enclosed nanosized extracellular vesicles, is a successful platform for providing a native membrane composition. This study reports an enzymatic exosome, which harbors native PH20 hyaluronidase (Exo-PH20), which is able to penetrate deeply into tumor foci via hyaluronan degradation, allowing tumor growth inhibition and increased T cell infiltration into the tumor. This exosome-based strategy is developed to overcome the immunosuppressive and anticancer therapy-resistant tumor microenvironment, which is characterized by an overly accumulated extracellular matrix. Notably, this engineered exosome with the native glycosylphosphatidylinositol-anchored form of hyaluronidase has a higher enzymatic activity than a truncated form of the recombinant protein. In addition, the exosome-mediated codelivery of PH20 hyaluronidase and a chemotherapeutic (doxorubicin) efficiently inhibits tumor growth. This exosome is designed to degrade hyaluronan, thereby augmenting nanoparticle penetration and drug diffusion. The results thus show that this is a promising exosome-based platform that harbors not only a membrane-associated enzyme with high activity but also therapeutic payloads.
Keywords: CANCER-THERAPY; EXTRACELLULAR VESICLES; HYALURONAN; SPERM; MICROENVIRONMENT; PH-20; NANOPARTICLES; NANOMEDICINE; PROGRESSION; BIOGENESIS